RNA- temperature-sensitive mutants of vesicular stomatitis virus: L-protein thermosensitivity accounts for transcriptase restriction of group I mutants. - Hunt, D M (1976)
In vitro transcriptase activity of three group I temperature-sensitive (ts) mutants of vesicular stomatitis virus restricted at 39 C was restored by L-protein fractions derived from wild-type (wt) vesicular stomatitis virion nucleo-capsids. Soluble NS protein from wt nucleocapsids did not reconstitute restricted transcriptions of the group I RNA-ts mutants. NS protein activity, but not L protein activity, was purified from the group I ts mutants; this NS fraction always displayed the wt phenotype in reconstitution assays. Neither the L nor the NS protein was capable of restoring the defective transcriptive activity of the group IV vesicular stomatitis virus mutant ts W16B.